Study on the decision support system of techniques and tactics in net sports and the application in Beijing Olympic Games - Yu, L.; Ling, P.; Zhang, H. (2010)
The techniques and tactics in net sports are the main factors of winning, while the key technology is the analysis of techniques and tactics and decision support. Using artificial intelligence, data mining and decision support technology, based on the development of multimedia and interactive data acquisition system and intelligent analysis system for the techniques and tactics in net sports, the decision support system of techniques and tactics in net sports is studied and developed. This achievement has been successfully used in table tennis team, badminton team, women's tennis team, volleyball team for women in 2008 Beijing Olympic Games, and the application effects are significant.